2009
DOI: 10.1038/eye.2009.222
|View full text |Cite
|
Sign up to set email alerts
|

Surgically induced astigmatism after 23-gauge transconjunctival sutureless vitrectomy

Abstract: Purpose: To evaluate surgically induced astigmatism (SIA) after 23-gauge transconjunctival sutureless vitrectomy (23GTSV). Methods: We studied 56 patients (56 eyes) who underwent 23GTSV between January 2006 and December 2007 and who underwent preoperative and 1-and 3-4-months postoperative corneal topography. Fifteen of the 56 patients underwent combined 23GTSV and cataract surgery. SIA was evaluated with Naeser's polar method using the simulated keratometric values obtained with corneal topography. Preoperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Postoperative cataract formation in the first month is less common in the absence of an intraoperative lens touch [12]. Postoperative astigmatism is demonstrated to be higher with the 20-G system, and it may be attributed to the sclera cautery and suturing at the entry port [13][14][15][16]. Increased postoperative inflammation with the 20-G system has been reported by several studies [5,6,17], which may be explained by the increased surgery duration and the required conjunctival opening with bleeding of conjunctival and episcleral vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative cataract formation in the first month is less common in the absence of an intraoperative lens touch [12]. Postoperative astigmatism is demonstrated to be higher with the 20-G system, and it may be attributed to the sclera cautery and suturing at the entry port [13][14][15][16]. Increased postoperative inflammation with the 20-G system has been reported by several studies [5,6,17], which may be explained by the increased surgery duration and the required conjunctival opening with bleeding of conjunctival and episcleral vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Amplitudes and changes in surgically induced astigmatism in our study were comparable with those in previous reports. 15,16 …”
Section: Postoperative Astigmatismmentioning
confidence: 98%
“…More recently, several authors have reported successful anatomic and visual outcomes with transconjunctival sutureless vitrectomy (TSV) in eyes with different vitreoretinal disorders, such as epiretinal membranes [13][14][15][16][17][18][19], macular holes [13,[15][16][17][18][19], vitreous hemorrhage [13,15,16,19,20], and proliferative diabetic retinopathy [13,16,17,19]. This technique gained favor with many vitreoretinal surgeons since complication rates are considered comparable to those reported with 20-gauge (20-G) systems [12,13,17], with less induced astigmatism [14,21] and reduced patient discomfort [18] but conflicting results concerning less surgically induced inflammation [14,22]. All of these studies suggest that 23-G instrumentation is safe and effective for performing vitreoretinal surgery.…”
Section: Introductionmentioning
confidence: 95%